2023
DOI: 10.1097/ju.0000000000003442
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Pelvic Lymph Node Dissection in Prostate Cancer Patients Diagnosed in the Era of Magnetic Resonance Imaging–targeted Biopsy: A Study That Challenges the Dogma

Abstract: Purpose:Bilateral extended pelvic lymph node dissection at the time of radical prostatectomy is the current standard of care if pelvic lymph node dissection is indicated; often, however, pelvic lymph node dissection is performed in pN0 disease. With the more accurate staging achieved with magnetic resonance imaging–targeted biopsies for prostate cancer diagnosis, the indication for bilateral extended pelvic lymph node dissection may be revised. We aimed to assess the feasibility of unilateral extended pelvic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The ongoing debate in the PCa field regarding ipsi- and contralateral LNI, coupled with emerging studies on sentinel LN mapping, particularly heightens the relevance of our investigation [ 15 , 16 , 35 , 36 , 37 ]. Bilateral pelvic lymphadenectomy performed during RP remains the gold standard for nodal staging [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ongoing debate in the PCa field regarding ipsi- and contralateral LNI, coupled with emerging studies on sentinel LN mapping, particularly heightens the relevance of our investigation [ 15 , 16 , 35 , 36 , 37 ]. Bilateral pelvic lymphadenectomy performed during RP remains the gold standard for nodal staging [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, a growing perspective suggests that a subset of patients may benefit from unilateral PLND. A recent investigation conducted by Martini et al identified the absence of high-risk disease features as a potential characteristic that might offer substantial benefits to patients undergoing ipsilateral PLND while omitting contralateral LNs [ 15 ]. Future investigations could enhance the process of patient selection for unilateral lymphadenectomy by incorporating additional factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Therefore, Martini et al investigated reducing bilateral ePLND to unilateral ePLND in selected cases, without compromising short-term oncologic outcomes. 2 In their novel nomogram, based on a multi-institutional data set from 19 tertiary referral centers, the rate of lymph node invasion (LNI) was 13% in both development and validation cohorts. Very well according to the authors' hypothesis, LNI was predominantly found on the ipsilateral side of the prostatic lobe with the worst disease features and yielded an impressive area under the curve of 84%.…”
Section: Editorial Commentmentioning
confidence: 99%
“…We appreciate the comment by Würnschimmel et al on our article on unilateral pelvic lymph node dissection (PLND). 1 First of all, the reader should note that the manuscript does not have a development/validation subdivision, as per advice of the statistical reviewers our main analyses changed during the review process. The figures/rates reported by Würnschimmel et al refer to an older version of the manuscript.…”
mentioning
confidence: 99%